PERBANDINGAN KEMAMPUAN BERPIKIR KRITIS MENGGUNAKAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN MODEL PEMBELAJARAN LANGSUNG SISWA KELAS VIII SMP NEGERI 5 KOTA JAMBI - Siti Mahmudah; Harman Harman; Sri Dewi (PHI: Jurnal Pendidikan Matematika, 2018)
Abstract: The ability to think critically is a form of thinking ability that needs to be developed in order to solve problems, formulate conclusions, collect possibilities, and make decisions when using all those skills effectively in the right context and type. The ability to think critically can encourage students to come up with new ideas or thoughts about a problem. Developing students' critical thinking skills can help students make conclusions by considering data and facts that occur in the field. This research is an experimental research with research design using experimental design Posttest Only Control Design. The population in this study is all students of class VIII SMPN 5 Kota Jambi consisting of eleven classes. While the sample is the students of class VIII C as the experimental class and class VIII J as the control class taken by random sampling. From the result of data analysis conducted on two samples obtained the average value of critical thinking ability of experimental class 71,36 with standard deviation 16,17 and mean value of critical thinking skill of class of 63,82 with standard deviation 15,58, and result hypothesis test obtained tcount 2.067 and ttable 1.67 at the level of real α is 0,05. From the calculation result it can be seen that tcount is more than ttable, so H0 is rejected and H1 accepted. Based on the final result, it can be concluded that there is a comparison of students' critical thinking ability taught by using Contextual Teaching and Learning model is higher than the critical thinking ability of students taught by using direct learning model.Keywords: Critical Thinking Skills, Contextual Teaching and Learning Model, and Direct Learning Model